Understanding Public Debates : What Literary Studies Can Do. - Gurr, Jens Martin. (Taylor & Francis Group, 2024)
Understanding Public Debates presents case studies including Milton's Paradise Lost and P.B. Shelley's 1820 Reform essay to explore how texts stage these debates by means of multiple perspectives, narrative situations, or ambiguities.